Growth of Chlamydia pneumoniae Is Enhanced in Cells with Impaired Mitochondrial Function - Käding, Nadja; Kaufhold, Inga; Müller, Constanze; Szaszák, Marta; Shima, Kensuke; Weinmaier, Thomas; Lomas, Rodrigo; Conesa, Ana; Schmitt-Kopplin, Philippe; Rattei, Thomas; Rupp, Jan (Frontiers in Cellular and Infection Microbiology, 2017)
Effective growth and replication of obligate intracellular pathogens depend on host cell metabolism. How this is connected to host cell mitochondrial function has not been studied so far. Recent studies suggest that growth of intracellular bacteria such as Chlamydia pneumoniae is enhanced in a low oxygen environment, arguing for a particular mechanistic role of the mitochondrial respiration in controlling intracellular progeny. Metabolic changes in C. pneumoniae infected epithelial cells were analyzed under normoxic (O2≈20%) and hypoxic conditions (O2<3%). We observed that infection of epithelial cells with C. pneumoniae under normoxia impaired mitochondrial function characterized by an enhanced mitochondrial membrane potential and ROS generation. Knockdown and mutation of the host cell ATP synthase resulted in an increased chlamydial replication already under normoxic conditions. As expected, cell hyperpolarization was observed in non-infected control cells cultured under hypoxic conditions, which was beneficial for C. pneumoniae growth. Taken together, functional and genetically encoded mitochondrial dysfunction strongly promotes intracellular growth of C. pneumoniae.